A bibliometric analysis of agarwood research, 1959-2021 - Hashim, Yumi Zuhanis Has-Yun; Samsudin, Nurhusna; Ahmad, Anis Najiha; Mohd Said, Norsabrina; Gill, Chris I.R.; Mohamad Tormizi, Ummu Athiyah; Ishak, Nur Iffah; Mohd Rozali, Nur Erina Syafiqa (2022)
Agarwood, is a fragrant resinous wood unique due to its peculiarity of being formed and harvested only from diseased trees of certain genus of Thymelaeaceae. It has survived years of history and established itself in the modern agarwood value chain. It is only logical that the progress has been fueled by scientific research carried out over the years. This current review is the first bibliometric study to uncover the agarwood research trend across the many themes. Bibliometric data were extracted from Scopus database in March 2021 using the search term ‘agarwood’ within the year 1959 to 2021. A total of 513 records were analysed using VosViewer and Publish or Perish software. Collectively, the articles were cited 6216 times with citations per year of 100.26 and h-index of 42. The top-contributing countries were China, Malaysia, Japan and Indonesia. Most of the publications were in the area of agricultural and biological sciences; biochemistry, genetics and molecular biology; chemistry; and pharmacology/pharmaceutics. The early years of agarwood research was focused on chemical compounds followed by studies on biological effects before the themes became varied in the last ten years. Critical knowledge gaps identified include safety of agarwood and its related materials, translational link between proof of concept and clinical applications as well as role of agarwood in socioeconomic development of a nation. Altogether, this work could be used as a landscape to chart the future research that leverage agarwood-producing trees as economic plant species towards progressive yet sustainable socioeconomic development and benefit to mankind.